ANALYSIS OF HUMAN IMMUNODEFICIENCY VIRUS GLYCOPROTEIN 160 AS A VACCINE CANDIDATE FOR B CELL EPITOPE OF ACQUIRED IMMUNODEFICIENCY SYNDROME - Yani Suryani (BERITA BIOLOGI, 2022)
An in silico study was conducted to analyze the potential of Human Immunodeficiency Virus (HIV) glycoprotein 160 as a candidate source of B cell subunit (epitope) vaccine for Acquired Immunodeficiency Syndrome (AIDS). The method used was immunoinformatics. The tools used were a set of laptop device, uniprot application, IEDB AR application and ToxinPred application. The materials used were glycoprotein sequences. The analysis results showed that there were 4 candidate peptides for B cell subunit (epitope) vaccines for AIDS, namely MRVMGIQ (Methionine, Arginine, Valine, Methionine, Glycine, Isoleucine, Glutamine, NMWKNNM (Asparagine, Methionine, Tryptophan, Lysine, Asparagine, Asparagine, Methionine), EIMGDIR (Glutamate, Isoleucine, Methionine, Glycine, Aspartic Acid, Isoleucine, and Arginine) and MWQRVGQ (Methionine, Tryptophan, Glutamine, Arginine, Valine, Glycine and Glutamine). All peptides are non-toxic so they are safe for the body